Effect of the COVID-19 pandemic on elective cataract surgery wait times - Toghi Eshghi, Saeed Reza; Cheema, Marvi; Damji, Karim F. (Canadian journal of ophthalmology, 2024)
Lengthy wait times for cataract surgery can negatively affect patients’ quality of life and increase the incidence of falls and depression. The COVID-19 pandemic has presented significant challenges to the delivery of elective cataract surgeries. The effects of the COVID-19 pandemic on cataract surgery wait times in the Alberta Health Services’ Edmonton zone were studied by examining the wait times before and during the pandemic. This study was conducted based on a retrospective population-based design. Data were compiled from a centralized database related to hospital-based cataract surgery (Royal Alexandra, Fort Saskatchewan, and WestView Health Centre) between April 2019 and March 2022 (i.e., 3 fiscal years). The average wait time for cataract surgery increased from 14.4 ± 1.4 weeks in 2019–2020 to 18.2 ± 2.7 weeks in 2020–2021 (p = 0.005) and then decreased to 11.5 ± 1.3 in 2021–2022 (p < 0.001). The number of completed surgeries decreased from 13,103 in 2019–200 to 9,308 (p = 0.09) and 10,365 (p = 0.1) during the next 2 years. The annual operating room time for scheduled cases was reduced to 4463 hours (p = 0.42) and 4552 hours (p = 0.15) during the pandemic compared with 5541 hours before the pandemic. However, the average waitlist size decreased from 6629 at the end of 2019–200 to 6122 (p = 0.029) and 4011 (p < 0.001) during the next 2 years. The COVID-19 pandemic resulted in significantly increased average wait times for elective cataract surgery during the first year of the pandemic. Because of a reduction of the waitlist size, the wait times decreased during the second year of the pandemic. La prolongation du temps d'attente avant une chirurgie de la cataracte risque d'avoir des effets négatifs sur la qualité de vie des patients et d'accroître l'incidence de chutes et de dépression. La pandémie de COVID-19 a posé de sérieux défis quant à la réalisation des chirurgies de la cataracte sans caractère d'urgence. On a donc examiné, grâce aux données du ministère de la santé de l'Alberta, les effets de la pandémie sur le temps d'attente avant une chirurgie de la cataracte dans la région d'Edmonton en comparant les temps d'attente avant et pendant la pandémie. Il s'agissait d'une étude fondée sur une population rétrospective. Les données provenaient d'une base de données centralisée portant sur les chirurgies de la cataracte réalisées en milieu hospitalier (Hôpital Royal Alexandra, Hôpital communautaire de Fort Saskatchewan et Centre de santé WestView) entre avril 2019 et mars 2022 (soit 3 années financières). L'attente moyenne avant une chirurgie de la cataracte est passée de 14,4 ± 1,4 semaines en 2019–2020 à 18,2 ± 2,7 semaines en 2020–2021 (p = 0,005) pour redescendre à 11,5 ± 1,3 semaines en 2021–2022 (p < 0,001). Le nombre de chirurgies réalisées est passé de 13 103 en 2019–2020 à 9308 (p = 0,09) et à 10 365 (p = 0,1) au cours des 2 années suivantes, respectivement. Le nombre d'heures de bloc opératoire réservées aux cas prévus chaque année a chuté à 4463 heures (p = 0,42) et à 4552 heures (p = 0,15) pendant la pandémie, comparativement à 5541 heures avant la pandémie. Cela dit, le nombre moyen de patients en attente d'une chirurgie est passé de 6629 à la fin de 2019–2020 à 6122 (p = 0,029) et à 4011 (p < 0,001) au cours des 2 années suivantes, respectivement. Le temps d'attente moyen précédant une chirurgie de la cataracte sans caractère d'urgence a significativement augmenté pendant la première année de la pandémie de COVID-19. Or, le temps d'attente a diminué pendant la deuxième année de la pandémie, vu la réduction du nombre de patients en attente d'une chirurgie.